PENGEMBANGAN E- MODUL BERBASIS FLIPPBOOK 3D UNTUK MENINGKATKAN HASIL BELAJARSISWA PADA MATA PELAJARAN IPS DI UPTD SMP NEGERI 1GUNUNGSITOLI - WAU, ROSARIA JINI; LAOLI, BEZISOKHI; LASE, ASALI; HAREFA, YEARNING (CENDEKIA: Jurnal Ilmu Pengetahuan, 2024)
This research is based on the researcher's observation on the implementation of grade VII learning at UPTD SMP Negeri 1 Gunungsitoli. which has been experiencing problems in the learning process, so that students' interest in learning is still lacking, especially in social studies subjects. The objectives of the research are: (1) to find out the development of 3D-flippbook-based e-modules to improve student learning outcomes (2) to find out the feasibility of 3D-flippbook-based e-modules to improve student learning outcomes. (3) to determine the effectiveness of 3D flippbook-based e-modules to improve student learning outcomes. This study uses the research and development (R&D) method used to produce a specific product, and test the effectiveness of the product. The feasibility test of this media is based on the acquisition of material experts, media experts, linguists, using the validation sheet of material experts, media experts, and linguists, the results of the study stated that the Flippbook 3D-based e-module on economic activity materials by material experts obtained a percentage of 0.96% by linguists of 94.5% and media experts of 0.96% which each has very valid criteria. For the results of the individual test, a percentage of 77% was obtained with very practical criteria and in the field test, a percentage of 82% was obtained with very practical criteria. and on the effectiveness of learning media using learning outcome tests with the percentage of student learning completeness reaching 75% with effective criteria. ABSTRAKPenelitian ini dilatar belakangi dari pengamatan peneliti pada pelaksanaan pembelajaran kelas VII di UPTD SMP Negeri 1 Gunungsitoli. yang selama ini mengalami permasalahan dalam proses pembelajaran, sehingga minat belajar siswa masih kurang khususnya dalam mata pelajaran IPS. Adapun tujuan dari penelitian yaitu: (1) untuk mengetahui pengembangan e-modul berbasis flippbook 3D untuk meningkatkan hasil belajar peserta didik  (2) untuk mengetahui  kelayakan e-modul berbasis flippbook 3D untuk meningkatkan hasil belajar peserta didik. (3) untuk mengetahui  keefektifan e-modul berbasis flippbook 3D untuk meningkatkan hasil belajar peserta didik. Jenis penelitian ini adalah peneitian pengembangan. Penelitian ini menggunakan metode research and development (R&D) metode penelitian yang digunakan untuk menghasilkan produk tertentu, dan menguji keefektifan produk tersebut. Uji kelayakan media ini berdasarkan peniaian ahli materi, ahli media, ahli bahasa, dengan menggunakan lembar validasi ahli materi, ahli media, dan ahli bahasa, hasil penelitian menyatakan bahwa e-modul berbasis Flippbook 3D pada materi kegiatan ekonomi oleh ahli materi diperoleh presentase 0,96%  oleh ahli bahasa sebesar 94,5%  ahli media sebesar 0,96%  yang masing-masing berkriteria sangat valid. Untuk hasil pada uji perorangan didapatkan presentase sebesar  77% dengan kriteria sangat praktis dan pada uji lapangan didapatkan presentase 82% dengan kriteria sangat praktis, dan pada efektifitas media pembelajaran menggunakan tes hasil belajar dengan presentase ketuntasan belajar peserta didik mencapai 75%  dengan kriteria efektif.